2019
DOI: 10.1108/ijph-06-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model on reintegration after prison in Norway

Abstract: Purpose Many offenders struggle when attempting to reintegrate into society after release from prison, and the conditions they face after release often lead to reoffending. The purpose of this paper is to present a conceptual model on reintegration after prison. The model has the potential to guide practitioners in their understanding of the relationships between welfare services and the agency of the offender. Design/methodology/approach The model was developed from a small-scale study in the Norwegian Crim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
4
15
0
1
Order By: Relevance
“…The participants described the multifaceted needs of offenders, the support needed from a variety of welfare professions and agencies, and the importance of different professions and agencies collaborating to provide the necessary quality of welfare service during this vulnerable transition phase (Theme 1). These views are supported by other Norwegian studies (Friestad & Kjeldberg, 2009;Hansen, 2015;Larsen et al, 2019). Larsen et al (2019) found in their small-scale study that offenders' experiences of support from the welfare services during vulnerable periods, such as reintegration after prison, varied, both within and between services.…”
Section: The Offender's Dependence On Interprofessional and Interagency Collaboration In Reintegration After Prisonsupporting
confidence: 60%
See 3 more Smart Citations
“…The participants described the multifaceted needs of offenders, the support needed from a variety of welfare professions and agencies, and the importance of different professions and agencies collaborating to provide the necessary quality of welfare service during this vulnerable transition phase (Theme 1). These views are supported by other Norwegian studies (Friestad & Kjeldberg, 2009;Hansen, 2015;Larsen et al, 2019). Larsen et al (2019) found in their small-scale study that offenders' experiences of support from the welfare services during vulnerable periods, such as reintegration after prison, varied, both within and between services.…”
Section: The Offender's Dependence On Interprofessional and Interagency Collaboration In Reintegration After Prisonsupporting
confidence: 60%
“…These views are supported by other Norwegian studies (Friestad & Kjeldberg, 2009;Hansen, 2015;Larsen et al, 2019). Larsen et al (2019) found in their small-scale study that offenders' experiences of support from the welfare services during vulnerable periods, such as reintegration after prison, varied, both within and between services. Moreover, in the Larsen et al study (2019), the offenders reported that they found themselves floundering in the gap between prison and community.…”
Section: The Offender's Dependence On Interprofessional and Interagency Collaboration In Reintegration After Prisonsupporting
confidence: 60%
See 2 more Smart Citations
“…Det er imidlertid mye som tyder på at dagens velferdstjenester harmonerer dårlig med innsattes og løslattes psykososiale behov (Larsen et al, 2019). Johnsen og Fridhov (2018) og Todd-Kvam og Ugelvik (2019) poengterer at det er en stor utfordring å koordinere alle relevante tjenester for å sikre en god tilbakeføringsprosess.…”
Section: Bakgrunnunclassified